Coronary Thermodilution Waveforms After Acute Reperfused ST‐Segment–Elevation Myocardial Infarction: Relation to Microvascular Obstruction and Prognosis. Issue 15 (7th August 2018) - Yew, Shu Ning; Carrick, David; Corcoran, David; Ahmed, Nadeem; Carberry, Jaclyn; Teng Yue May, Vannesa; McEntegart, Margaret; Petrie, Mark C.; Eteiba, Hany; Lindsay, Mitchell; Hood, Stuart; Watkins, Stuart; et al.
Abstract : Background: Invasive measures of microvascular resistance in the culprit coronary artery have potential for risk stratification in acute ST‐segment–elevation myocardial infarction. We aimed to investigate the pathological and prognostic significance of coronary thermodilution waveforms using a diagnostic guidewire. Methods and Results: Coronary thermodilution was measured at the end of percutaneous coronary intervention, (PCI) and contrast‐enhanced cardiac magnetic resonance imaging (MRI) was intended on day 2 and 6 months later to assess left ventricular (LV) function and pathology. All‐cause death or first heart failure hospitalization was a pre‐specified outcome (median follow‐up duration 1469 days). Thermodilution recordings underwent core laboratory assessment. A total of 278 patients with acute ST‐segment elevation myocardial infarction EMI (72% male, 59±11 years) had coronary thermodilution measurements classified as narrow unimodal (n=143 [51%]), wide unimodal (n=100 [36%]), or bimodal (n=35 [13%]). Microvascular obstruction and myocardial hemorrhage were associated with the thermodilution waveform pattern ( P =0.007 and 0.011, respectively), and both pathologies were more prevalent in patients with a bimodal morphology. On multivariate analysis with baseline characteristics, thermodilution waveform status was a multivariable associate of microvascular obstruction (odds ratio [95% confidence interval]=5.29 [1.73, 16.22];, P =0.004) and myocardial hemorrhage (3.45 [1.16, 10.26]; P =0.026), but the relationship was not significant when index of microvascular resistance (IMR) >40 or change in index of microvascular resistance (5 per unit) was included. However, a bimodal thermodilution waveform was independently associated with all‐cause death and hospitalization for heart failure (odds ratio [95% confidence interval]=2.70 [1.10, 6.63]; P =0.031), independent of index of microvascular resistance>40, ST‐segment resolution, and TIMI (Thrombolysis in Myocardial Infarction) Myocardial Perfusion Grade. Conclusions: The thermodilution waveform in the culprit coronary artery is a biomarker of prognosis and may be useful for risk stratification immediately after reperfusion therapy.